INTERESTING ORGANIZATION OF FOREIGN LANGUAGE LESSONS - Dilrabo Adizova Rahmonovna (American Journals Publishing, 2022)
This article provides feedback on the use of game technologies in English language classes.
Keywords: game, technology, education, ball, objects, category, kitchen